Method for manufacturing a solid battery and solid battery

JP2026166321APending Publication Date: 2026-10-14HONDA MOTOR CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025059190
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0032】 本発明の固体電池の製造方法では、複数の極群を形成し、前記複数の極群の抵抗値の変動係数が所定の範囲内となるように、前記複数の極群から前記設定抵抗極群を複数枚選択する。そして、設定抵抗極群を積層して極群積層体を形成し、極群積層体を化成する。したがって、本発明の固体電池の製造方法によれば、極群積層体の有する設定抵抗極群の抵抗値のバラツキは十分に少ないものとなる。このため、複数の極群を積層した極群積層体を含む固体電池を歩留まりよく製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166321000002
    Figure 2026166321000002
  • Figure 2026166321000003
    Figure 2026166321000003
  • Figure 2026166321000001
    Figure 2026166321000001
Patent Text Reader

Abstract

To provide a method for manufacturing solid-state batteries that can produce solid-state batteries containing a stacked electrode group, which is formed by stacking multiple electrode groups, with a high yield. [Solution] A method for manufacturing a solid battery, comprising: a first step of forming a plurality of electrode groups including a positive electrode layer, a solid electrolyte layer, and a negative electrode layer; a second step of selecting a plurality of set resistance electrode groups from the plurality of electrode groups such that the coefficient of variation of the resistance values ​​of the plurality of electrode groups is within a predetermined range; a third step of stacking the set resistance electrode groups to form an electrode group stack; and a fourth step of chemically forming the electrode group stack.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for manufacturing a solid-state battery and to a solid-state battery. [Background technology]

[0002] In recent years, research and development has been conducted on solid-state batteries that contribute to energy efficiency, in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy. In solid-state batteries, there is a growing demand for further improvements in energy density. As a method for improving the energy density of solid-state batteries, the use of an electrode group laminate, which consists of multiple electrode groups including a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, is being investigated.

[0003] Patent Document 1 describes a cell structure comprising a sheet-like cathode, a sheet-like anode, and a sheet-like solid electrolyte layer interposed between the cathode and the anode. Patent Document 1 also describes that the solid electrolyte layer of the cell structure is laminated on the anode, and the cathode is laminated on the solid electrolyte layer. Furthermore, Patent Document 1 describes a cell structure with low resistance, where the relationship Rc / Ra ≥ 0.3 is satisfied between the resistance Rc of the cathode and the resistance Ra of the anode and solid electrolyte layer, the cathode contains a first metal oxide having a perovskite-type crystal structure, and the thickness of the cathode is greater than 15 μm and less than or equal to 30 μm.

[0004] Patent Document 2 describes a solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, as well as a method for manufacturing a solid-state battery. The solid-state battery described in Patent Document 2 is described as comprising an aluminum layer in contact with the solid electrolyte layer, a lithium layer, and an aluminum-lithium alloy layer disposed between the aluminum layer and the lithium layer. Patent Document 2 describes that because it comprises an aluminum layer in contact with the solid electrolyte layer and a lithium layer in contact with the aluminum layer, it is possible to provide a solid-state battery in which the discharge capacity does not easily decrease and the DCR resistance does not easily increase even after repeated charging and discharging.

[0005] Patent Document 3 describes a battery stack that can suppress an increase in internal resistance. Specifically, it describes a battery stack having one or more electrode bodies stacked in the order of a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, a positive electrode terminal electrically connected to the positive electrode layer, a negative electrode terminal electrically connected to the negative electrode layer, a positive electrode metal sputtered layer disposed between the power generation element and the positive electrode terminal, a negative electrode metal sputtered layer disposed between the power generation element and the negative electrode terminal, and an outer casing. In the battery stack described in Patent Document 3, the positive electrode terminal and the negative electrode terminal are sintered or fused metal bodies, the power generation element contains sulfur, the material of the positive electrode metal sputtered layer and / or the negative electrode metal sputtered layer is at least one selected from the group including gold, platinum, nickel, or stainless steel, and the power generation element is sealed by the outer casing, the negative electrode terminal and the positive electrode terminal. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] International Publication No. 2019 / 171905 [Patent Document 2] International Publication No. 2019 / 151376 [Patent Document 3] Patent No. 7622706 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION

[0007] Incidentally, in the technical field related to solid-state batteries, when manufacturing a solid-state battery including an electrode group laminate in which a plurality of electrode groups are laminated, it is difficult to obtain a solid-state battery having predetermined performance, and improvement of manufacturing yield has been an issue.

[0008] The present application has been made in view of the above issues, and an object thereof is to provide a method for manufacturing a solid-state battery that can manufacture, with good yield, a solid-state battery including an electrode group laminate in which a plurality of electrode groups are laminated. And in turn, it contributes to energy efficiency improvement. Further, the present application aims to provide a solid-state battery that can be manufactured with good yield by using the method for manufacturing a solid-state battery of the present application. MEANS FOR SOLVING THE PROBLEMS

[0009] In order to solve the above issues, the following means are provided.

[0010] A method for manufacturing a solid-state battery according to a first aspect of the present invention includes a first step of forming a plurality of electrode groups (1) each including a positive electrode layer (11), a solid electrolyte layer (13), and a negative electrode layer (12), a second step of selecting a plurality of set-resistance electrode groups (1a) from the plurality of electrode groups (1) such that a coefficient of variation in resistance values of the plurality of electrode groups (1) falls within a predetermined range, a third step of laminating the set-resistance electrode groups (1a) to form an electrode group laminate (10), and a fourth step of subjecting the electrode group laminate (10) to chemical conversion.

[0011] In the first embodiment of the method for manufacturing a solid-state battery, multiple electrode groups (1) are formed, and multiple set resistance electrode groups (1a) are selected from the multiple electrode groups (1) such that the coefficient of variation of the resistance values ​​of the multiple electrode groups (1) is within a predetermined range. Then, the set resistance electrode groups (1a) are stacked to form an electrode group laminate (10), and the electrode group laminate (10) is chemically formed. Therefore, according to the first embodiment of the method for manufacturing a solid-state battery, the variation in the resistance values ​​of the set resistance electrode groups (1a) in the electrode group laminate (10) is sufficiently small. As a result, a solid-state battery with sufficient capacity is easily obtained, and solid-state batteries including an electrode group laminate (10) formed by stacking multiple electrode groups (1) can be manufactured with a high yield.

[0012] A second aspect of the present invention relates to a method for manufacturing a solid battery, wherein the resistance value in the manufacturing method of the first aspect is an AC resistance value. In the second embodiment of the solid-state battery manufacturing method, the coefficient of variation of the AC resistance value is used as the coefficient of variation of the resistance value of the multiple electrode groups (1), so the resistance value of each electrode group (1) can be measured in a shorter time compared to the case where the DC resistance value is used. As a result, the coefficient of variation of the resistance value of each electrode group (1) can be calculated in a short time, and the variation in the resistance value of each set resistance electrode group (1a) forming the electrode group stack (10) can be efficiently suppressed.

[0013] A third aspect of the present invention is a method for manufacturing a solid battery, in which, in the second step of the manufacturing method of the first aspect described above, multiple set resistance electrode groups (1a) are selected from the plurality of electrode groups (1) in the fourth step such that the AC resistance value of the plurality of electrode groups (1) falls within a predetermined range calculated based on the set DC resistance value of the electrode group stack (10) after chemical formation and discharge for 10 seconds.

[0014] In the third embodiment of the solid battery manufacturing method, multiple electrode groups (1a) are selected from the plurality of electrode groups (1) such that the AC resistance values ​​of the plurality of electrode groups (1) fall within a predetermined range calculated based on the set DC resistance value of the electrode group stack (10). As a result, after chemical formation, the electrode group stack (10) is more likely to be formed in which the DC resistance value (DCR) after 10 seconds of discharge is within the range of the set DC resistance value, and the yield of the electrode group stack (10) at the end of chemical formation is improved.

[0015] A fourth aspect of the present invention is a method for manufacturing a solid battery, in which, in the second step of the manufacturing method of the first aspect described above, a set resistance electrode group (1a) is selected from a plurality of electrode groups (1) such that the set DC resistance value when the electrode group laminate (10) is formed and discharged for 10 seconds can be approximated as a function of the AC resistance value of the electrode group (1).

[0016] In the fourth embodiment of the method for manufacturing a solid-state battery, in the second step, multiple electrode groups (1a) are selected from the plurality of electrode groups (1) such that the set DC resistance value when the electrode group stack (10) is formed and discharged for 10 seconds can be approximated as a function of the AC resistance value of the electrode group (1). As a result, electrode group stacks (10) in which the DC resistance value (DCR) when discharged for 10 seconds after formation is within the range of the set DC resistance value are more easily formed. Consequently, the yield of electrode group stacks (10) at the end of the formation process is further improved.

[0017] A fifth aspect of the present invention is a method for manufacturing a solid battery, in which, in the second step of the manufacturing method of the first aspect described above, the electrode group stack (10) is formed and a set DC resistance value is discharged for 10 seconds, and a set number of electrode groups (1a) are selected from the plurality of electrode groups (1) so that the relationship between the set DC resistance value and the AC resistance value of the electrode group (1) can be linearly approximated.

[0018] In the manufacturing method of the solid battery according to the fifth embodiment, in the second step, a electrode group stack (10) is formed, and multiple electrode groups (1a) with the set resistance are selected from the plurality of electrode groups (1) so that the relationship between the set DC resistance value when discharged for 10 seconds and the AC resistance value of the electrode group (1) can be linearly approximated. As a result, after formation, it becomes easier to form an electrode group stack (10) in which the DC resistance value (DCR) when discharged for 10 seconds is within the range of the set DC resistance value.

[0019] A sixth aspect of the present invention is a method for manufacturing a solid battery, wherein the resistance value is an AC resistance value and the coefficient of variation of the resistance value is 15% or less, in the manufacturing method of the first aspect described above. A seventh aspect of the present invention is a method for manufacturing a solid battery, wherein the resistance value is an AC resistance value and the coefficient of variation of the resistance value is 10% or less, in the manufacturing method of the first aspect described above.

[0020] In the manufacturing method of a solid-state battery according to the sixth embodiment and the manufacturing method of a solid-state battery according to the seventh embodiment, the resistance value is the AC resistance value, and the coefficient of variation of the resistance value is 15% or less or 10% or less. Therefore, the variation in the resistance value of each set resistance electrode group (1a) forming the electrode group stack (10) is more effectively suppressed, making it easier to obtain a solid-state battery with a large capacity.

[0021] The eighth aspect of the present invention is a method for manufacturing a solid battery, in which, in the fourth step of the manufacturing method of the first aspect described above, the electrode group laminate (10) is chemically formed to produce an electrode group laminate (10) in which the coefficient of variation of the DC resistance values ​​of the plurality of set resistance electrode groups (1a) forming the electrode group laminate (10) is 10% or less. In the manufacturing method of the solid battery according to the eighth aspect, a solid battery with excellent characteristics can be obtained in which the coefficient of variation of the DC resistance values ​​of the plurality of set resistance electrode groups (1a) forming the electrode group stack (10) is 10% or less.

[0022] A manufacturing method for a solid-state battery according to the ninth aspect of the present invention is to chemically transform the electrode group laminate (10) in the fourth step of the manufacturing method according to the first aspect, thereby achieving a DC resistance of 20 Ωcm at a temperature of 60°C. 2The following polar group laminate (10) is manufactured. In the manufacturing method of a solid-state battery according to the ninth embodiment, the DC resistance value at a temperature of 60°C is 20 Ωcm. 2 A solid-state battery with excellent properties can be obtained, which includes the following electrode group stack (10).

[0023] A method for manufacturing a solid battery according to the tenth aspect of the present invention involves, in the second step of the manufacturing method according to the first aspect, selecting multiple set resistance electrode groups (1a) from the plurality of electrode groups (1) such that the coefficient of variation of the capacity of the plurality of set resistance electrode groups (1a) falls within a predetermined range. In the manufacturing method of the solid battery according to the tenth embodiment, in the second step, multiple set resistance electrode groups (1a) are selected from the multiple electrode groups (1) such that the coefficient of variation of the capacity of the multiple set resistance electrode groups (1a) is within a predetermined range, thereby obtaining an electrode group stack (10) with less variation in the capacity of the multiple set resistance electrode groups 1a.

[0024] The manufacturing method for a solid battery according to the eleventh aspect of the present invention is such that the coefficient of variation of the capacity is 5% or less, as in the manufacturing method according to the tenth aspect. The method for manufacturing a solid battery according to the twelfth aspect of the present invention is such that the coefficient of variation of the capacity is 3% or less, as in the manufacturing method according to the tenth aspect.

[0025] In the manufacturing method of a solid-state battery according to the eleventh embodiment and the manufacturing method of a solid-state battery according to the twelfth embodiment, multiple set resistance electrode groups (1a) are selected from the plurality of electrode groups (1) such that the coefficient of variation of capacity is 5% or less or 3% or less, thereby obtaining an electrode group laminate (10) with less variation in the capacity of the plurality of set resistance electrode groups 1a.

[0026] A thirteenth aspect of the present invention is a method for manufacturing a solid battery, wherein, in the manufacturing method of the first aspect described above, the negative electrode layer (12) comprises lithium metal or a lithium alloy. In the manufacturing method of the solid-state battery according to the thirteenth embodiment, the variation in the resistance values ​​of the set resistance electrode groups (1a) of the electrode group stack (10) is sufficiently small, and uniformity of the battery reaction in each set resistance electrode group (1a) is easily ensured. Furthermore, a solid-state battery can be obtained in which the negative electrode layer (12) contains lithium metal or a lithium alloy. As a result, the energy density improvement effect due to the inclusion of lithium metal or a lithium alloy in the negative electrode layer (12) is more effectively obtained, and a solid-state battery with higher energy density can be obtained.

[0027] A solid-state battery according to the fourteenth aspect of the present invention was manufactured by the method for manufacturing a solid-state battery described in the first aspect above. The solid-state battery of the fourteenth embodiment is manufactured by the method for manufacturing a solid-state battery described in the first embodiment above, and therefore includes a stacked electrode group (10) in which a plurality of set resistance electrode groups (1a) are stacked, and can be manufactured with a high yield.

[0028] A solid battery according to a fifteenth aspect of the present invention includes an electrode group laminate (10) in which a plurality of electrode groups (1) including a positive electrode layer (11), a solid electrolyte layer (13), and a negative electrode layer (12) are stacked, The specific capacity per positive electrode active material of the electrode group laminate (10) is 150 mAh / g or more. The DC resistance of the aforementioned polar group laminate (10) at 60°C after 10 seconds of discharge is 18 Ωcm. 2 The following applies:

[0029] The solid-state battery of the fifteenth embodiment includes an electrode group stack (10) in which a plurality of electrode groups (1) are stacked, wherein the specific capacity per positive electrode active material of the electrode group stack (10) is 150 mAh / g or more, and the DC resistance of the electrode group stack (10) at 60°C after 10 seconds of discharge is 18 Ωcm 2 It possesses excellent characteristics for the following reasons.

[0030] A solid-state battery according to the sixteenth aspect of the present invention is a solid-state battery according to the fifteenth aspect described above, wherein the specific capacity per positive electrode active material of the electrode group stack (10) is 150 mAh / g or more. The DC resistance of the aforementioned polar group laminate (10) at 60°C after 10 seconds of discharge is 2 Ωcm. 2 The above is 17Ωcm 2 The following applies:

[0031] The solid-state battery of the sixteenth embodiment has a specific capacity per positive electrode active material of the electrode group stack (10) of 150 mAh / g or more, and the DC resistance of the electrode group stack (10) at 60°C after 10 seconds of discharge is 2 Ωcm 2 The above is 17Ωcm 2 Therefore, it has superior characteristics. [Effects of the Invention]

[0032] In the method for manufacturing a solid-state battery of the present invention, multiple electrode groups are formed, and multiple set resistance electrode groups are selected from the multiple electrode groups such that the coefficient of variation of the resistance values ​​of the multiple electrode groups is within a predetermined range. Then, the set resistance electrode groups are stacked to form an electrode group stack, and the electrode group stack is chemically formed. Therefore, according to the method for manufacturing a solid-state battery of the present invention, the variation in the resistance values ​​of the set resistance electrode groups in the electrode group stack is sufficiently small. As a result, solid-state batteries including electrode group stacks formed by stacking multiple electrode groups can be manufactured with a high yield. [Brief explanation of the drawing]

[0033] [Figure 1] Figure 1 is a schematic cross-sectional view illustrating an example of a polarity stack of a solid-state battery according to this embodiment. [Figure 2] Figure 2 is a scatter plot showing the relationship between the AC resistance (ACR) of the electrode groups used as materials for 10 electrode group laminate samples and the DC resistance (DCR) of the 10 electrode group laminate samples after chemical formation and discharge for 10 seconds. [Modes for carrying out the invention]

[0034] To solve the above problems and to manufacture solid-state batteries including electrode stacks with multiple electrode groups stacked on top of each other with good yield, the inventors focused on the process of forming electrode stacks by stacking multiple electrode groups within the manufacturing process of solid-state batteries and conducted diligent research. As a result, the inventors found that increasing the number of stacked electrode groups, which form an electrode group stack where multiple electrode groups are connected in parallel, in order to improve the energy density of a solid-state battery makes it difficult to obtain a solid-state battery with the desired performance and reduces the manufacturing yield. Therefore, they focused on the process of stacking multiple electrode groups to form an electrode group stack and conducted further investigations.

[0035] As a result, it was found that in solid-state batteries containing electrode stacks with many electrode groups connected in parallel, the variation in resistance values ​​between electrode groups is large, making it difficult to obtain solid-state batteries with the desired performance, and resulting in a low manufacturing yield. This is because, in electrode stacks with many electrode groups connected in parallel, if even one of the electrode groups has a resistance value higher than a predetermined value, abnormalities occur within the electrode stack due to charging and discharging.

[0036] Therefore, the inventors diligently conducted research to improve the uniformity of resistance values ​​in each pole group forming the pole group stack. As a result, they found that by selecting multiple set resistance pole groups from multiple pole groups and stacking them so that the coefficient of variation of the resistance values ​​of the multiple pole groups falls within a predetermined range, a pole group stack in which multiple set resistance pole groups are connected in parallel can be formed.

[0037] Because the polarity stack obtained in this way has little variation in the resistance values ​​of each polarity group contained within the stack, it is easy to obtain a solid-state battery with sufficient capacity. Furthermore, the inventors of the present invention have come up with the present invention after confirming that a solid battery including a stack of stacked electrode groups in which multiple electrode groups are connected in parallel can be manufactured with a high yield by forming multiple electrode groups, selecting multiple set resistance electrode groups from the multiple electrode groups so that the coefficient of variation of the resistance values ​​of the multiple electrode groups is within a predetermined range, and stacking them to form an electrode group stack in which multiple set resistance electrode groups are connected in parallel.

[0038] The method for manufacturing a solid-state battery and the solid-state battery of this embodiment will be described in detail below, with appropriate reference to the drawings. The drawings used in the following description may be enlarged for convenience in order to clearly illustrate the features of the present invention. Therefore, the dimensional ratios of each component may differ from those of the actual components. The materials, dimensions, etc., exemplified in the following description are examples only, and the present invention is not limited to them. It can be implemented with appropriate modifications without changing the essence of the invention.

[0039] [Solid battery] Figure 1 is a schematic cross-sectional view illustrating an example of a polarity stack of a solid-state battery according to this embodiment. The solid-state battery of this embodiment includes a polarity group stack 10 as shown in Figure 1, a restraining jig (not shown) for restraining the polarity group stack 10, and a case (outer casing (not shown)) for housing the polarity group stack 10.

[0040] The electrode group stack 10 of the solid-state battery of this embodiment is manufactured by the manufacturing method of the solid-state battery of this embodiment, which will be described later. As a restraining jig, known ones such as end plates can be used. Also, as a case, known ones that can be used as a case for a solid-state battery can be used.

[0041] (Polar group stack 10) As shown in Figure 1, the electrode group stack 10 is made up of multiple (three layers in Figure 1) electrode groups 1 (set resistance electrode groups 1a) stacked together. In this embodiment, the multiple electrode groups 1 forming the electrode group stack 10 are connected in parallel. Therefore, compared to, for example, the case where the multiple electrode groups 1 forming the electrode group stack 10 are connected in series, it is easier to predict the resistance value of the entire electrode group stack 10 from a single electrode group 1, and it becomes possible to manufacture large-capacity solid-state batteries with a high yield.

[0042] The number of layers of electrode group 1 in the electrode group stack 10 may be, for example, 5 layers, 7 layers, 12 layers, 27 layers, etc., and can be appropriately determined depending on the application of the solid-state battery, and is not particularly limited. The more layers of electrode group 1 there are, the more pronounced the effects of manufacturing using the solid-state battery manufacturing method of this embodiment, which will be described later, are, and is therefore preferable. Specifically, when the number of layers of electrode group 1 is 10 or more, the effects of using the manufacturing method of this embodiment become more pronounced.

[0043] Each electrode group 1 (set resistance electrode group 1a) forming the electrode group laminate 10 includes a positive electrode layer 11, a solid electrolyte layer 13, a negative electrode layer 12, and an insulating member 14. In this embodiment, as an example of a preferred electrode group 1, as shown in Figure 1, a case is described in which two positive electrode layers 11 are arranged facing each other within a frame-shaped insulating member 14, and a solid electrolyte layer 13 and a negative electrode layer 12 are arranged in this order on both sides in the thickness direction.

[0044] The positive electrode active material layer 11c of the positive electrode layer 11, the negative electrode active material layer 12c of the negative electrode layer 12, the solid electrolyte layer 13, and the insulating member 14, which form electrode group 1 as shown in Figure 1, all have a roughly rectangular outer shape in plan view. In electrode group 1, in plan view, the positive electrode active material layer 11c, the negative electrode active material layer 12c, and the outer surface of the negative electrode side solid electrolyte layer 13b of the solid electrolyte layer 13 are arranged inside the outer surface of the insulating member 14, and the positive electrode active material layer 11c and the positive electrode side solid electrolyte layer 13a of the solid electrolyte layer 13 are arranged inside the outer surfaces of the negative electrode active material layer 12c and the negative electrode side solid electrolyte layer 13b. Furthermore, in the pole group 1 shown in Figure 1, the positive electrode current collector tab 11b of the positive electrode layer 11 and the negative electrode current collector tab 12b of the negative electrode layer 12 are arranged to extend in opposite directions (left-right direction in Figure 1) relative to the pole group laminate 10.

[0045] [Positive electrode layer 11] As the positive electrode layer 11, a known positive electrode layer 11 used as the positive electrode of a solid-state battery can be applied. The positive electrode layer 11 has, for example, a sheet-shaped positive electrode current collector 11a and a sheet-shaped positive electrode active material layer 11c.

[0046] In the electrode group laminate 10 shown in Figure 1, one positive electrode current collector 11a is positioned between the positive electrode active material layers 11c of the two positive electrode layers 11. In other words, the positive electrode active material layers 11c are positioned in contact with both sides of the one positive electrode current collector 11a. As a result, in the electrode group laminate 10 shown in Figure 1, one positive electrode current collector 11a also serves as the positive electrode current collector 11a for the two adjacent positive electrode layers 11.

[0047] The positive electrode current collector 11a is not particularly limited, and for example, metal foils such as stainless steel (S) foil and aluminum (Al) foil can be used. The positive electrode current collector 11a of the positive electrode layer 11 is electrically connected to a positive electrode current collector tab 11b that extends outward from the positive electrode current collector 11a and is integrally molded with the positive electrode current collector 11a.

[0048] The positive electrode current collector tab 11b does not have to be molded integrally with the positive electrode current collector 11a, and may be formed from a different material than the positive electrode current collector 11a. If the positive electrode current collector tab 11b is formed from a different material than the positive electrode current collector 11a, the positive electrode current collector tab 11b is electrically connected to the positive electrode current collector 11a by known methods such as welding or brazing.

[0049] The positive electrode active material layer 11c can contain a positive electrode active material known as a positive electrode active material for solid-state batteries. The positive electrode active material layer 11c may also contain a solid electrolyte, a conductive additive, a binder, etc., along with the positive electrode active material. As the positive electrode active material layer 11c, if the solid-state battery is a lithium-ion solid-state battery, for example, materials containing transition metal chalcogenides such as titanium disulfide, molybdenum disulfide, and niobium selenide, or transition metal oxides such as lithium nickelate (LiNiO2), lithium manganeseate (LiMnO2, LiMn2O4), and lithium cobaltate (LiCoO2) can be used.

[0050] The content of the positive electrode active material contained in the positive electrode active material layer 11c is preferably in the range of 60 mass% to 95 mass%, and more preferably in the range of 70 mass% to 85 mass%. When the content of the positive electrode active material is within the above range, in-plane resistance distribution can be suppressed even when the electrode group laminate 10 has higher output and / or a larger area.

[0051] The basis weight of the two positive electrode active material layers 11c included in each electrode group 1 is 10 mg / cm in total 2 ~80 mg / cm 2 is preferably within the range, and 28 mg / cm 2 ~65 mg / cm 2 is more preferably within the range. The total basis weight of the two positive electrode active material layers 11c included in the electrode group 1 is 10 mg / cm 2 or more, the electrode group 1 has high output. When the basis weight of the positive electrode active material layer 11c is 80 mg / cm 2 or less, the electrode group 1 has high capacity and can ensure the required output.

[0052] [Negative Electrode Layer 12] As the negative electrode layer 12, a known negative electrode layer 12 used as a negative electrode of a solid-state battery can be applied. The negative electrode layer 12 includes, for example, a sheet-shaped negative electrode current collector 12a and a sheet-shaped negative electrode active material layer 12c.

[0053] The negative electrode current collector 12a is not particularly limited, and for example, a metal foil such as a stainless steel (SUS) foil or a copper (Cu) foil can be used. The negative electrode current collector 12a of the negative electrode layer 12 extends outward from the negative electrode current collector 12a, and is electrically connected to a negative electrode current collector tab 12b formed integrally with the negative electrode current collector 12a.

[0054] The negative electrode current collector tab 12b does not need to be formed integrally with the negative electrode current collector 12a, and may be formed of a member different from the negative electrode current collector 12a. When the negative electrode current collector tab 12b is formed of a member different from the negative electrode current collector 12a, the negative electrode current collector tab 12b is electrically connected to the negative electrode current collector 12a by a known method such as welding or thermal welding.

[0055] As the negative electrode active material layer 12c, one containing a negative electrode active material known as a negative electrode active material for solid-state batteries can be used. As the negative electrode active material layer 12c, if the solid-state battery is a lithium-ion solid-state battery, for example, materials containing lithium metal, lithium alloy, metal oxide, metal sulfide, metal nitride, Si, SiO, graphite, hard carbon, soft carbon, etc. can be used. The negative electrode active material layer 12c preferably contains lithium metal or a lithium alloy in order to obtain a solid-state battery with high energy density.

[0056] More specifically, for example, if the negative electrode active material in the negative electrode active material layer 12c is made of a carbon material, lithium ions move in and out within the negative electrode active material layer. In contrast, in a negative electrode active material layer 12c containing lithium metal or a lithium alloy, lithium is deposited in the stacking direction of the lithium metal or lithium alloy. Therefore, when the negative electrode active material layer 12c contains lithium metal or a lithium alloy, if the variation in the resistance values ​​of the set resistance electrode group 1a is sufficiently small and the battery reaction in each set resistance electrode group 1a is uniform, lithium is more likely to be deposited more uniformly in the in-plane direction in the negative electrode layer 12 of each set resistance electrode group 1a. As a result, the energy density improvement effect due to the negative electrode active material layer 12c being a solid-state battery containing lithium metal or a lithium alloy can be obtained more effectively.

[0057] When the negative electrode active material layer 12c is made of lithium metal foil, the thickness of the lithium metal foil is preferably in the range of 1 μm to 30 μm, and more preferably in the range of 3 μm to 10 μm. When the thickness of the lithium metal foil is within the above range, electrode group 1 is obtained with high energy density and suppressed degradation of cycle performance.

[0058] [Solid electrolyte layer 13] As shown in Figure 1, the solid electrolyte layer 13 is laminated between the positive electrode layer 11 and the negative electrode layer 12. The solid electrolyte layer 13 in electrode group 1 shown in Figure 1 has a laminated structure in which two layers are laminated: a positive electrode side solid electrolyte layer 13a located on the positive electrode layer 11 side and a negative electrode side solid electrolyte layer 13b located on the negative electrode layer 12 side. The positive electrode side solid electrolyte layer 13a and the negative electrode side solid electrolyte layer 13b may be the same or different. If the positive electrode side solid electrolyte layer 13a and the negative electrode side solid electrolyte layer 13b are different, for example, one or more differences can be selected from thickness, planar shape, and material.

[0059] The positive electrode solid electrolyte layer 13a and the negative electrode solid electrolyte layer 13b contain a solid electrolyte material. The positive electrode solid electrolyte layer 13a and the negative electrode solid electrolyte layer 13b facilitate ion transfer between the positive electrode active material in the positive electrode active material layer 11c and the negative electrode active material in the negative electrode active material layer 12c via the solid electrolyte material.

[0060] The solid electrolyte material contained in the positive electrode solid electrolyte layer 13a and the negative electrode solid electrolyte layer 13b is not particularly limited, and known solid electrolyte materials can be used. Specifically, sulfide solid electrolyte materials, oxide solid electrolyte materials, nitride solid electrolyte materials, halide solid electrolyte materials, etc. can be used as the solid electrolyte material, and sulfide solid electrolyte materials are preferred.

[0061] The content of the solid electrolyte material in the positive electrode solid electrolyte layer 13a is preferably in the range of 95% to 99% by mass. When the content of the solid electrolyte material is within the above range, the formation of voids in the positive electrode solid electrolyte layer 13a can be suppressed, the resistance of the positive electrode solid electrolyte layer 13a can be reduced, and the electrodeposition of lithium in the positive electrode solid electrolyte layer 13a can be suppressed.

[0062] The thickness of the positive electrode side solid electrolyte layer 13a is preferably in the range of 0.5 μm to 15 μm, and more preferably in the range of 1 μm to 5 μm. When the thickness of the positive electrode side solid electrolyte layer 13a is within the above range, the interface formation between the positive electrode layer 11 and the positive electrode active material layer 11c is good, and the interfacial resistance with the positive electrode active material layer 11c can be suppressed.

[0063] The content of the solid electrolyte material in the negative electrode solid electrolyte layer 13b is preferably in the range of 90% to 99% by mass. When the content of the solid electrolyte material is within the above range, the formation of voids in the negative electrode solid electrolyte layer 13b can be suppressed, and the decrease in ionic conductivity in the negative electrode solid electrolyte layer 13b can be suppressed.

[0064] The thickness of the negative electrode solid electrolyte layer 13b is preferably in the range of 15 μm to 120 μm, and more preferably in the range of 20 μm to 60 μm. When the thickness of the negative electrode solid electrolyte layer 13b is within the above range, the mechanical strength of the negative electrode solid electrolyte layer 13b becomes sufficiently high, resulting in an electrode group laminate 10 with good durability.

[0065] [Insulating material 14] As shown in Figure 1, each electrode group 1 forming the electrode group laminate 10 has a frame-shaped insulating member 14 that horizontally covers the positive electrode active material layer 11c and the positive electrode side solid electrolyte layer 13a of the positive electrode layer 11. The insulating member 14 and the positive electrode active material layer 11c may be an integrated member or separate members.

[0066] In this embodiment, the electrode group stack 10 of the solid-state battery has an insulating member 14 covering the entire circumference of the positive electrode active material layer 11c of the positive electrode layer 11, which is approximately rectangular in plan view. This ensures insulation between the positive electrode layer 11 and the negative electrode layer 12, resulting in a safe solid-state battery. Furthermore, because the insulating member 14 is arranged to surround the outer circumference of the positive electrode active material layer 11c of the positive electrode layer 11, even if a horizontal displacement occurs in the set resistance electrode group 1a, the thickness of the insulating member 14 helps to ensure uniformity of the pressure applied to each set resistance electrode group 1a. As a result, it becomes easier to obtain a solid-state battery with predetermined performance.

[0067] The material constituting the insulating member 14 can be any insulating material and is not particularly limited. Specifically, for example, resins such as Nomex®, polyethylene terephthalate, polystyrene, polyvinyl chloride, polycarbonate, polyethylene, polypropylene, and polyimide, fluororesins such as polyvinylidene fluoride and polytetrafluoroethylene, ceramics such as alumina, and insulating materials made by mixing these materials can be used.

[0068] The solid-state battery of this embodiment has a specific capacity of 150 mAh / g or more for the electrode group stack 10. The upper limit of the specific capacity of the electrode group stack 10 is not particularly limited, but may be, for example, 250 mAh / g or less, or 220 mAh / g or less. In the solid-state battery of this embodiment, the variation in resistance values ​​of each electrode group 1 forming the electrode group stack 10 is suppressed, so that the specific capacity of the electrode group stack 10 is equivalent to the specific capacity of the electrode group 1 (single cell) before stacking.

[0069] In this embodiment, the solid-state battery has a DC resistance of 18 Ωcm at a temperature of 60°C when the electrode group stack 10 is discharged for 10 seconds. 2 The following is the DC resistance of the polar group laminate 10 at a temperature of 60°C after 10 seconds of discharge: 2 Ωcm 2 The above is 17Ωcm 2 The following is also acceptable.

[0070] In this embodiment, a solid-state battery having electrode group 1 as shown in Figure 1 was described as an example. However, electrode group 1 only needs to include a positive electrode layer 11, a solid electrolyte layer 13, and a negative electrode layer 12, and may not include an insulating member 14, or it may have only one of the two insulating members 14. Furthermore, although this embodiment has described an example in which the insulating member 14 covers the entire circumference of the positive electrode active material layer 11c and the positive electrode side solid electrolyte layer 13a of the positive electrode layer 11 in a plan view, the insulating member 14 may be arranged only on a part of the outer periphery of the positive electrode layer 11.

[0071] Furthermore, the shape and stacking order of the positive electrode layer 11, the solid electrolyte layer 13, and the negative electrode layer 12 forming the electrode group 1 are not limited to the example of electrode group 1 shown in Figure 1. For example, two negative electrode layers may be arranged opposite a negative electrode current collector, with a solid electrolyte layer and a positive electrode layer arranged in that order on both sides in the thickness direction. Furthermore, in the embodiments described above, the example given was that in pole group 1, one positive electrode current collector 11a also serves as the positive electrode current collector 11a for two adjacent positive electrode layers 11. However, each of the two positive electrode layers 11 may also have a positive electrode current collector 11a.

[0072] Furthermore, in this embodiment, it is also preferable to use an electrode group 1b having an intermediate layer 15 between the negative electrode active material layer 12c and the negative electrode side solid electrolyte layer 13b of the negative electrode layer 12, as shown in Figure 2, as each electrode group forming the electrode group laminate 10.

[0073] [Middle class 15] As the intermediate layer 15, for example, it can be made of particles consisting of metal elements that form an alloy with Li, such as SiC, SnC, AgC, and MgC, and carbon; Li alloy foils such as LiIn, LiAg, LiAl, and LiMg; or a resin containing a liquid that contains a Li ion conductor, such as an ionic liquid.

[0074] In this embodiment, when each electrode group forming the electrode group laminate 10 is an electrode group 1b having an intermediate layer between the negative electrode layer 12 and the negative electrode-side solid electrolyte layer 13b, the precipitation and dissolution of Li metal becomes more uniform, and the performance variation of each electrode group 1b included in the electrode group laminate 10 can be suppressed more effectively.

[0075] [Manufacturing method for solid-state batteries] In this embodiment, the method for manufacturing a solid-state battery will be explained using the example of manufacturing a solid-state battery that includes the electrode group stack 10 shown in Figure 1. In the manufacturing method of the solid battery of this embodiment, the following steps (first step) to (fourth step) are performed.

[0076] (first step) In the first step, multiple pole groups 1 shown in Figure 1 are formed. First, a positive electrode active material layer 11c is formed on both sides of a current collector sheet that will become the positive electrode current collector 11a by a known method, such as applying a positive electrode composite material containing the positive electrode active material using a die coater and drying it.

[0077] Next, a solid electrolyte material is transferred to both the front and back surfaces of the positive electrode current collector 11a having the positive electrode active material layer 11c formed by the above method, using a known method. Then, a roll press is used to form a positive electrode side solid electrolyte layer 13a integrated with the positive electrode active material layer 11c, and it is punched out into a predetermined shape. This forms a positive electrode piece on both the front and back surfaces of a single positive electrode current collector 11a, consisting of a positive electrode active material layer 11c, a positive electrode side solid electrolyte layer 13a, and a positive electrode current collector tab 11b that is integrally molded with the positive electrode current collector 11a.

[0078] In this embodiment, the case in which the solid electrolyte material is transferred to both the front and back surfaces of the positive electrode current collector 11a and then the current collector sheet is punched out into a predetermined shape was described as an example. However, it is also possible to punch out the current collector sheet on which the positive electrode active material layer 11c is provided before transferring the solid electrolyte material to both the front and back surfaces of the positive electrode current collector 11a, and then transfer the solid electrolyte material to both the front and back surfaces of the positive electrode current collector 11a.

[0079] Furthermore, a negative electrode active material layer 12c is formed on one surface of a current collector sheet that will become the negative electrode current collector 12a by a known method, and a negative electrode layer 12 having a negative electrode current collector tab 12b integrally molded with the negative electrode current collector 12a is formed by punching out the negative electrode active material layer 12c. Subsequently, a solid electrolyte material is transferred onto the negative electrode layer 12 formed on one surface of the negative electrode current collector 12a by a known method. Then, a negative electrode side solid electrolyte layer 13b integrated with the negative electrode active material layer 12c is formed using a roll press. This forms a negative electrode piece consisting of a negative electrode active material layer 12c installed on one side of the negative electrode current collector 12a, a negative electrode side solid electrolyte layer 13b formed thereon, and a positive electrode current collector tab 11b molded integrally with the negative electrode current collector 12a.

[0080] Next, a frame-shaped insulating member 14 is placed on the negative electrode side solid electrolyte layer 13b of the negative electrode piece formed in this manner, such that the negative electrode active material layer 12c is on the inside of the outer surface of the insulating member 14 in a plan view. If the insulating member 14 is a separate component from the positive electrode active material layer 11c, the insulating member 14 can be formed, for example, by processing an insulating material into a predetermined shape and size, and then arranging it to cover at least a portion of the periphery of the positive electrode layer 11.

[0081] The above describes the case where the insulating member 14 is a separate component from the positive electrode active material layer 11c. However, when the insulating member 14 is an integrated component with the positive electrode active material layer 11c, the insulating member 14 can be formed, for example, by the method shown below. That is, it can be formed by dissolving an insulating material in a solvent such as an organic solvent to make a slurry, coating this slurry around the positive electrode layer 11 of the positive electrode piece, and drying it.

[0082] Subsequently, one of the two positive electrode layers 11 and positive electrode-side solid electrolyte layer 13a of the positive electrode piece is housed inside the insulating member 14, and the insulating member 14 horizontally covers the periphery of one of the positive electrode layers 11. At this time, the positive electrode current collector tab 11b of the positive electrode piece and the negative electrode current collector tab 12b of the negative electrode layer 12 are arranged to extend in opposite directions (left-right direction in Figure 1) relative to the electrode group laminate 10.

[0083] Next, a frame-shaped insulating member 14 is placed on the positive electrode side solid electrolyte layer 13a of the positive electrode piece that is not housed inside the insulating member 14, thereby housing the positive electrode layer 11 and the positive electrode side solid electrolyte layer 13a inside the insulating member 14. Next, the negative electrode piece is positioned with the negative electrode solid electrolyte layer 13b facing the positive electrode solid electrolyte layer 13a. At this time, in a plan view, the negative electrode active material layer 12c is positioned on the inside of the outer surface of the frame-shaped insulating member 14.

[0084] After that, for example, a uniaxial press is performed at a pressure of 100 MPa to 120 MPa for 1 to 10 minutes. Through the above process, multiple pole groups 1 shown in Figure 1 are formed.

[0085] (Second process) In the second step, the resistance value of each of the multiple electrode groups 1 formed in the first step is measured. The standard deviation of the obtained measurement results is then calculated and divided by the mean value of the measurement results to calculate the coefficient of variation of the resistance values ​​of the multiple electrode groups 1. Here, the coefficient of variation means the value obtained by dividing the standard deviation (σ) by the mean value.

[0086] Then, multiple set resistance electrode groups 1a are selected from the multiple electrode groups 1 so that the coefficient of variation of the resistance values ​​of the multiple electrode groups 1 fall within a predetermined range. This suppresses the variation in resistance values ​​of each set resistance electrode group 1a forming the electrode group stack 10, making it easier to obtain a solid-state battery with sufficient capacity.

[0087] In the second step, it is preferable to measure the AC resistance (ACR) as the resistance value of each pole group 1. When the AC resistance is measured as the resistance value of pole group 1, the resistance value can be measured in a shorter time compared to when the DC resistance value is used. Therefore, the coefficient of variation of the resistance value of each pole group 1 can be calculated in a short time, and the variation in the resistance value of each set resistance pole group 1a forming the pole group laminate 10 can be efficiently suppressed. For measuring AC resistance, known methods can be used, such as measuring the current amplitude response under conditions of a frequency of 1 kHz and a voltage amplitude of 10 mV.

[0088] In this embodiment, when AC resistance (ACR) is used as the resistance value of each electrode group 1, it is preferable to select multiple set resistance electrode groups 1a from multiple electrode groups 1 so that the coefficient of variation of the resistance value is 15% or less, and it is more preferable to select multiple set resistance electrode groups 1a from multiple electrode groups 1 so that the coefficient of variation of the resistance value is 10% or less. This more effectively suppresses the variation in resistance value of each set resistance electrode group 1a forming the electrode group stack 10, making it easier to obtain a solid-state battery with a large capacity.

[0089] Furthermore, the inventors believe that in the fourth step described later, in order to improve the yield of the electrode group laminate 10 at the time the chemical conversion is completed, it is preferable to evaluate the characteristics of the set resistance electrode group 1a used as the material for the electrode group laminate 10 and reduce the number of electrode group laminates 10 that do not achieve the predetermined performance at the time the chemical conversion is completed.

[0090] The inventors then focused on the relationship between the characteristics of the set resistance electrode group 1a used as the material for the electrode group laminate 10 and the characteristics of the electrode group laminate 10 after chemical formation, and conducted extensive research. As a result, we found that there is a correlation between the AC resistance value (ACR) of electrode group 1 used as the material for the electrode group laminate 10 and the DC resistance value (DCR) of the electrode group laminate 10 after chemical conversion and discharge for 10 seconds.

[0091] In this specification, "the DC resistance value of the polar group laminate after chemical conversion and 10 seconds of discharge" means the value calculated by measuring the DC resistance value (DCR) of the polar group laminate 10 under the measurement conditions shown below, after performing chemical conversion under the conditions shown below.

[0092] (Conditions for the chemical formation of polar group laminate 10) As a chemical treatment for the polar group laminate 10, charging and discharging were performed at a temperature of 60°C, a constraining load of 3 MPa, a C rate of 0.1 C, and in the range of 2.65 V-4.3 V. (Measurement conditions for the DC resistance (DCR) of the polar group laminate 10) The electrode group laminate 10 after chemical formation was adjusted to a state of charge (SOC) of 50%, and the voltage drop was measured when it was discharged from a state of charge (SOC) of 50% at 0.7C for 10 seconds. The calculation was then performed using these results.

[0093] Based on the above correlation, the inventors investigated a method for producing a high yield of electrode group laminates 10 in which the DC resistance value (DCR) of the electrode group laminate 10 after chemical conversion and discharge for 10 seconds is within a predetermined target value, which is a set DC resistance value. As a result, it was found that in the second step, after chemical conversion, multiple plates with AC resistance values ​​(ACR) within a predetermined range should be selected from the multiple electrode groups 1, which are the materials for the electrode group laminate 10, as the set resistance electrode group 1a, so that the AC resistance value (ACR) falls within a predetermined range calculated based on the set DC resistance value (DCR) of the electrode group laminate 10 when discharged for 10 seconds.

[0094] Therefore, in this embodiment, in the second step, it is preferable to select multiple electrode groups 1a from the multiple electrode groups 1 such that the AC resistance values ​​of the multiple electrode groups 1 fall within a predetermined range calculated based on the set DC resistance value (DCR) of the electrode group laminate 10 after 10 seconds of discharge following chemical formation. This makes it easier to form an electrode group laminate 10 in which the DC resistance value (DCR) after 10 seconds of discharge following chemical formation is within the range of the set DC resistance value, and enables the production of the electrode group laminate 10 with a high yield.

[0095] Furthermore, the inventors have found that in the second step, by selecting multiple electrode groups 1a from multiple electrode groups 1 so that the set DC resistance value when the electrode group laminate 10 is formed and discharged for 10 seconds can be approximated as a function of the AC resistance value of electrode group 1, it becomes even easier to form an electrode group laminate 10 in which the DC resistance value (DCR) when discharged for 10 seconds after formation is within the range of the set DC resistance value.

[0096] The AC resistance value of electrode group 1, which can approximate the set DC resistance value when the electrode group laminate 10 is formed and discharged for 10 seconds, is, for example, the AC resistance value (ACR) (Ωcm) of the electrode group used as the material for the electrode group laminate 10. 2 ) and the set DC resistance (DCR) (Ωcm) at a temperature of 60°C after the formation of the polar group laminate 10 and a 10-second discharge. 2 The regression line shown by equation (1) below is a function that shows the relationship with ).

[0097] y = ax + b ... (1) (In equation (1), x is the AC resistance (ACR) (Ωcm) of the pole group used as the material for the pole group laminate 10. 2) is the set DC resistance (DCR) (Ωcm) at a temperature of 60°C after discharging for 10 seconds after the formation of the polar group laminate 10. 2 ) a and b are greater than 0. )

[0098] In equation (1), x is the AC resistance value (ACR) of the set resistance electrode group 1a selected from multiple electrode groups 1 as the material for the electrode group laminate 10, and is 20 Ωcm. 2 ~160Ωcm 2 Preferably, it is 40 Ωcm 2 ~160Ωcm 2 It is more preferable that the AC resistance value of the setting resistor group 1a is 20 Ω cm. 2 The above conditions are preferable from a productivity standpoint because they make it easier to obtain electrode group 1 with less variation in resistance values. The AC resistance value of the set resistance electrode group 1a is 160 Ωcm. 2 The following is preferable because it allows for the manufacture of a low-resistance polar group laminate 10.

[0099] The range of the coefficient of variation of the AC resistance (ACR) of the set resistance electrode group 1a selected from multiple electrode groups 1, represented by x in equation (1), is preferably 15% or less, more preferably 10% or less, and the smaller the better. When the range of the coefficient of variation of the AC resistance of the set resistance electrode group 1a is 15% or less, it becomes easier to obtain an electrode group laminate 10 with less variation in the resistance values ​​of the set resistance electrode group 1a.

[0100] In equation (1), y is the set DC resistance (Ωcm) at a temperature of 60°C after the polarity group laminate 10 has been chemically converted and discharged for 10 seconds. 2 ) and for example, 20 Ωcm 2 The following are also acceptable, 17Ωcm 2 The following are also acceptable, 15Ωcm 2 The following is also acceptable: y in equation (1) is 20 Ωcm 2 If the following conditions are met, then by selecting multiple electrode groups 1a from multiple electrode groups 1 such that the set resistance electrode group 1a is within the range that satisfies equation (1), the DC resistance (DCR) after 10 seconds of discharge following chemical formation is 20 Ωcm. 2The following properties make it easier to obtain polar group laminates (10) with superior characteristics.

[0101] In formula (1), a is preferably in the range of 1 to 20, and more preferably in the range of 2 to 10. In formula (1), b is preferably in the range of 0 to 10, and more preferably in the range of 1 to 5.

[0102] The coefficient of determination R in equation (1) 2 It is preferable that the coefficient of determination R is in the range of 0.5 or more and 1.0 or less. 2 From a productivity standpoint, it may be in the range of 0.5 to 0.9. The coefficient of determination R in equation (1) 2 When the value is 0.5 or greater, the relationship between x and y in equation (1) shows a strong correlation with the regression line in equation (1). As a result, it becomes easier to form electrode group laminates 10 whose DC resistance (DCR) after 10 seconds of discharge following chemical conversion is within the set DC resistance range. Consequently, electrode group laminates 10 can be manufactured with a higher yield.

[0103] In the second step, it is preferable to select multiple electrode groups 1a from the multiple electrode groups 1 such that the AC resistance values ​​of the multiple electrode groups 1 fall within a predetermined range calculated based on the set DC resistance value of the electrode group laminate 10 after the chemical formation and discharge for 10 seconds. Specifically, for example, if the set DC resistance (DCR) of the electrode group laminate 10 after chemical conversion and 10 seconds of discharge is 5 Ωcm 2 Above 40Ωcm 2 The AC resistance from multiple pole groups 1 is 20 Ωcm, within the following range. 2 More than 160Ωcm 2 It is preferable to select one within the specified range.

[0104] Furthermore, in the second step, it is preferable to select multiple electrode groups 1a from multiple electrode groups 1 so that the set DC resistance value when the electrode group laminate 10 is formed and discharged for 10 seconds can be approximated as a function of the AC resistance value of electrode group 1. Specifically, for example, the set DC resistance (DCR) of the electrode group laminate 10 after 10 seconds of discharge is 5 Ωcm. 2 Above 40Ωcm 2 The AC resistance from multiple pole groups 1 is 20 Ωcm, within the following range. 2 More than 160Ωcm 2 It is preferable to select multiple electrode groups 1 within the specified range, and then further select multiple set resistance electrode groups 1a from among the multiple electrode groups 1 such that the correlation function between the AC resistance value (ACR) of the electrode group used as the material for the electrode group laminate 10 and the set DC resistance value (DCR) at a temperature of 60°C after the electrode group laminate 10 has been chemically converted and discharged for 10 seconds is 0.5 or higher.

[0105] The relationship between the AC resistance (ACR) of the pole group used as the material for the pole group laminate 10 and the DC resistance of the pole group laminate 10 after chemical conversion and 10 seconds of discharge is not limited to the linear approximation shown in equation (1), but may also be a polynomial approximation.

[0106] In the second step, it is preferable to select multiple set resistor electrode groups 1a from multiple electrode groups 1 such that the coefficient of variation of the capacitance of the multiple set resistor electrode groups 1a falls within a predetermined range. This results in an electrode group laminate 10 with less variation in the capacitance of the multiple set resistor electrode groups 1a. In this embodiment, it is preferable to select multiple setting resistance electrode groups 1a from multiple electrode groups 1 so that the coefficient of variation of capacitance is 5% or less, and it is more preferable to select multiple setting resistance electrode groups 1a from multiple electrode groups 1 so that the coefficient of variation of capacitance is 3% or less. By selecting multiple setting resistance electrode groups 1a from multiple electrode groups 1 so that the coefficient of variation of capacitance is 5% or less, an electrode group laminate 10 with less variation in the capacitance of the multiple setting resistance electrode groups 1a can be obtained.

[0107] In this embodiment, in the second step, the method for selecting multiple set resistor electrode groups 1a from multiple electrode groups 1 such that the coefficient of variation of the capacitance of the multiple set resistor electrode groups 1a falls within a predetermined range may be the method shown below. In other words, the basis weight of the positive electrode active material in the positive electrode active material layer 11c of the positive electrode layer 11 of electrode group 1 is correlated with the capacity of electrode group 1. Therefore, by selecting multiple set resistance electrode groups 1a from multiple electrode groups 1 such that the coefficient of variation of the basis weight of the positive electrode active material layer of multiple set resistance electrode groups 1a falls within a predetermined range, it is possible to select multiple set resistance electrode groups 1a whose capacity coefficients fall within a predetermined range.

[0108] Specifically, in the first step, the positive electrode active material layer 11c of the positive electrode layer 11 is formed, and the basis weight of the positive electrode active material in the positive electrode active material layer 11c is measured. Then, before laminating the positive electrode layer 11 with other components that will form electrode group 1, only the positive electrode layers 11 whose coefficient of variation of the basis weight of the positive electrode active material layer is within a predetermined range are selected from the manufactured positive electrode layers 11. Subsequently, using only the positive electrode layers 11 whose coefficient of variation of the basis weight of the positive electrode active material layer is within a predetermined range, the solid electrolyte layer 13, negative electrode layer 12, insulating member 14, etc. that constitute electrode group 1 are laminated to form multiple electrode groups 1. As a result, in the second step, all of the set resistance electrode groups 1a selected from the multiple electrode groups 1 have coefficients of variation of the positive electrode active material layer weight within a predetermined range, and consequently, the coefficients of variation of the capacitance of the multiple set resistance electrode groups 1a are within a predetermined range.

[0109] By using this method, it may be possible to reduce the effort required to form the pole group 1 that cannot be used as material for the pole group laminate 10, or to reduce the amount of solid electrolyte layer 13 and negative electrode layer 12 used to manufacture the pole group 1 that is not used as material for the pole group laminate 10.

[0110] (Third step) In the third step, the set resistor electrode group 1a is stacked. Next, the stacked sets of resistor electrode groups 1a are connected in parallel to form a set of electrode group stacks 10. Then, in the sets of resistor electrode groups 1a forming the set of electrode group stacks 10, the positive electrode current collector tabs 11b of the positive electrode layer 11 are electrically connected, and the negative electrode current collector tabs 12b of the negative electrode layer 12 are electrically connected.

[0111] Subsequently, the pole group laminate 10, in which multiple set resistance pole groups 1a are connected in parallel, is restrained using a known restraining jig (not shown), such as an end plate, and pressure is applied to the pole group laminate 10 in the stacking direction. The pressure (restraining load) applied to the pole group laminate 10 in the stacking direction can be in the range of 0.5 MPa to 5 MPa, and is preferably in the range of 1 MPa to 3 MPa. Subsequently, the pole group laminate 10, which is restrained by the restraining jig, is housed in a case (not shown).

[0112] (Fourth step) In the fourth step, the polar group laminate 10 is formed. Examples of methods for forming the polar group laminate 10 include a method of charging and discharging at a temperature of 60°C, a constraining load of 3 MPa, a C rate of 0.1C, and a voltage range of 2.65V-4.3V.

[0113] In the fourth step, it is preferable to manufacture an electrode group laminate 10 in which the coefficient of variation of the DC resistance values ​​(DCR) of the multiple set resistance electrode groups 1a forming the electrode group laminate 10 is 10% or less. In this embodiment, in the second step, multiple set resistance electrode groups 1a are selected from multiple electrode groups 1 so that the coefficient of variation of the resistance values ​​of the multiple electrode groups 1 are within a predetermined range, so that the multiple set resistance electrode groups 1a forming the electrode group laminate 10 have little variation in resistance values. For this reason, in the fourth step, it is easy to obtain an electrode group laminate 10 in which the coefficient of variation of the DC resistance values ​​(DCR) of the multiple set resistance electrode groups 1a is 10% or less.

[0114] Specifically, in the second step, if multiple set resistance electrode groups 1a are selected from multiple electrode groups 1 such that the AC resistance value of the multiple electrode groups 1 has a coefficient of variation of 10% or less, then the coefficient of variation of the DC resistance value (DCR) of the multiple set resistance electrode groups 1a forming the electrode group stack 10 will be 10% or less. Such a solid-state battery is preferable because it has excellent characteristics. The coefficient of variation of the DC resistance value (DCR) of the multiple electrode groups 1 forming the electrode group stack 10 after chemical formation is preferably 9.9% or less, and more preferably 9.8% or less.

[0115] Furthermore, in the fourth step, by forming the polar group laminate 10, the DC resistance (DCR) at a temperature of 60°C is 20 Ωcm. 2 It is preferable to manufacture the electrode group stack 10 as follows. Such a solid-state battery is preferable because it has excellent properties. The DC resistance (DCR) of the electrode group stack 10 is 17 Ωcm at a temperature of 60°C. 2 The following is preferable: 15 Ωcm 2 The following is more preferable:

[0116] Furthermore, in the fourth step, by forming the polar group laminate 10, the DC resistance (DCR) at a temperature of 25°C is 70 Ωcm. 2 It is also preferable to manufacture the following polar group laminate 10. By performing the above steps, the solid-state battery of this embodiment can be obtained.

[0117] The embodiments of the present invention have been described above, but these embodiments are provided to facilitate understanding of the present invention and do not limit it. The present invention can be modified and improved without departing from its spirit and claims, and of course, equivalents thereof are included in the present invention. [Examples]

[0118] (Example of experiment) Eleven of each of the seven types of pole group 1 that meet the following conditions were manufactured, and the AC resistance (ACR) of each pole group 1 was measured. From the multiple pole groups 1 whose AC resistance was measured, those with an AC resistance of 0.05Ω to 2.5Ω at 1kHz were selected, and 1 to 5 of them were connected in parallel to manufacture 10 samples of pole group stacks that simulate stacked pole groups 1.

[0119] The 10 polar group laminate samples obtained in this manner were each subjected to chemical formation under the conditions shown below, and their DC resistance (DCR) was measured under the conditions shown below.

[0120] (Conditions of the polar groups used as materials for 10 polar group laminate samples) As electrode groups, electrode group 1 shown in Figure 1, which has a positive electrode layer 11, a solid electrolyte layer 13, a negative electrode layer 12, and an insulating member 14, and electrode group 1b shown in Figure 2, which has a positive electrode layer 11, a solid electrolyte layer 13, a negative electrode layer 12, an insulating member 14, and an intermediate layer 15 were used.

[0121] The positive electrode layer 11 consisted of a positive electrode current collector 11a made of aluminum (Al) foil and a positive electrode active material layer 11c containing an argyrodite-type sulfide solid electrolyte as the positive electrode active material. The content of the positive electrode active material in the positive electrode active material layer 11c was set to within the range of 60% to 80% by mass. The basis weight of the positive electrode active material layer 11c was 10 mg / cm³. 2 ~40 mg / cm³ 2 It was set within the range.

[0122] The negative electrode layer 12 consisted of a negative electrode current collector 12a made of copper (Cu) foil and a negative electrode active material layer 12c made of lithium metal foil. The lithium metal foil used had a thickness in the range of 5 μm to 30 μm.

[0123] As the positive electrode solid electrolyte layer 13a, a solid electrolyte material with a content in the range of 98% to 99% by mass and a thickness in the range of 1 μm to 30 μm was used. As the negative electrode solid electrolyte layer 13b, a solid electrolyte material was used with a content in the range of 95% to 99% by mass and a thickness in the range of 30 μm to 120 μm.

[0124] In electrode group 1 shown in Figure 1, the insulating material 14 was made of Nomex®. In electrode group 1b shown in Figure 2, an alumina material was used as the insulating member 14. As shown in Figure 2, the intermediate layer 15 in pole group 1b was made of SiC.

[0125] (Conditions for chemical conversion of 10 samples of polar group laminates) Ten polar group laminate samples were subjected to chemical conversion treatment at a temperature of 60°C, a constraining load of 3 MPa, a C rate of 0.1 C, and charging and discharging in the range of 2.65 V-4.3 V.

[0126] (Measurement conditions for DC resistance (DCR) of 10 samples of polar group laminates) Ten samples of the electrode group laminate after chemical formation were adjusted to a state of charge (SOC) of 50%, and the voltage drop was measured when discharged from a state of charge (SOC) of 50% at 0.7C for 10 seconds. The results were then used to calculate the voltage drop.

[0127] Next, using the DC resistance (DCR) values ​​of the 10 electrode group laminate samples after chemical formation measured in this manner, a scatter plot was created showing the relationship between the AC resistance (ACR) values ​​of the electrode groups used as materials for the 10 electrode group laminate samples and the DC resistance (DCR) values ​​of the 10 electrode group laminate samples after chemical formation and 10 seconds of discharge.

[0128] As a result, it was found that there is a positive correlation between the AC resistance value (ACR) (X in equation (1A) below) of pole group 1, which was used as the material for 10 pole group laminate samples, and the DC resistance value (DCR) (Y in equation (1A) below) of the 10 pole group laminate samples measured under the above conditions after chemical formation, as shown by the regression line in equation (1A) below. Y = 8.83X + 4.86 (1A)

[0129] [Example 1] A solid-state battery of Example 1, including a pole group stack 10 in which 12 layers of the set resistance pole group 1a shown in Figure 1 are stacked, was manufactured using the method described below.

[0130] (first step) In the first step, 40 pole groups 1 were formed. Each electrode group 1 was formed by the following method. First, a current collector sheet made of 12 μm thick aluminum (Al) foil was prepared to serve as the positive electrode current collector 11a. A positive electrode active material layer 11c with a thickness of 100 μm was formed on both sides of the current collector sheet by applying a positive electrode composite material with the following composition using a die coater and drying it.

[0131] The basis weight of the positive electrode active material in the positive electrode active material layer 11c of each of the two positive electrode layers 11 forming one electrode group 1 is 54.8 mg / cm³, which is the target total basis weight. 2 After forming the positive electrode active material layer 11c on both sides of the current collector sheet, the basis weight of each layer was measured.

[0132] "Composition of positive electrode composite material" Cathode active material: NCM622; 60% by mass Conductive additive: Li100 (product name; manufactured by Denka Co., Ltd.) 35, 8% by mass Solid electrolyte: Algyrodite-type sulfide solid electrolyte (D50 0.7 μm) 2,7% by mass Binder: Fluorine-based rubber binder, 1.3% by mass

[0133] Next, using the results of measuring the basis weight of the positive electrode active material in the positive electrode current collector 11a having the positive electrode active material layer 11c formed by the above method, multiple positive electrode current collectors 11a having a specific positive electrode active material layer 11c were selected such that the coefficient of variation of the basis weight of the positive electrode active material layer, which is the sum of the positive electrode active material layers 11c in each of the two positive electrode layers 11, is 0.8% or less.

[0134] Next, a solid electrolyte material consisting of 1.3 mass% solid electrolyte: argyrodite-type sulfide solid electrolyte (D50 of 0.7 μm) and binder: fluorine-based rubber binder was transferred to both the front and back surfaces of a positive electrode current collector 11a having multiple positive electrode active material layers 11c, each having a coefficient of variation of variation of positive electrode active material layer weight within the range of 0.8% or less. This solid electrolyte material was then roll-pressed to form a 3 μm thick positive electrode-side solid electrolyte layer 13a integrated with the positive electrode active material layers 11c.

[0135] Subsequently, by punching out a predetermined shape, positive electrode pieces consisting of a positive electrode active material layer 11c, a positive electrode side solid electrolyte layer 13a, and a positive electrode current collector tab 11b integrally molded with the positive electrode current collector 11a are formed on both the front and back surfaces of a single positive electrode current collector 11a.

[0136] Furthermore, a current collector sheet made of copper (Cu) foil with a thickness of 10 μm was prepared to serve as the negative electrode current collector 12a. A negative electrode active material layer 12c made of lithium metal with a thickness of 20 μm was formed on one surface of the current collector sheet, and by punching this out, a negative electrode layer 12 having a negative electrode current collector tab 12b integrally molded with the negative electrode current collector 12a was formed.

[0137] Subsequently, a solid electrolyte material consisting of 97.3% by mass of a solid electrolyte: argyrodite-type sulfide solid electrolyte (D50 of 0.7 μm) and a binder: fluorine-based rubber binder was transferred onto the negative electrode layer 12 formed on one side of the negative electrode current collector 12a, and roll-pressed to form a 100 μm thick negative electrode-side solid electrolyte layer 13b integrated with the negative electrode active material layer 12c.

[0138] This resulted in the formation of a negative electrode piece consisting of a negative electrode active material layer 12c installed on one side of the negative electrode current collector 12a, a negative electrode side solid electrolyte layer 13b formed thereon, and a positive electrode current collector tab 11b molded integrally with the negative electrode current collector 12a.

[0139] Next, an insulating member 14 was placed on the negative electrode solid electrolyte layer 13b side of the negative electrode piece formed in this manner. The insulating member 14 was a frame-shaped object made of Nomex® with a horizontal width of 11 mm and a thickness of 1.3 mm. The insulating member 14 was installed so that, in a plan view, the negative electrode active material layer 12c was positioned inside the outer surface of the insulating member 14.

[0140] Subsequently, one of the two positive electrode layers 11 and the positive electrode-side solid electrolyte layer 13a of the positive electrode piece was housed inside the insulating member 14, and the insulating member 14 horizontally covered the periphery of one of the positive electrode layers 11. At this time, the positive electrode current collector tab 11b of the positive electrode piece and the negative electrode current collector tab 12b of the negative electrode layer 12 were arranged to extend in opposite directions (left-right direction in Figure 1) relative to the electrode group laminate 10.

[0141] Next, a frame-shaped insulating member 14 is placed on the positive electrode side solid electrolyte layer 13a of the positive electrode piece that is not housed inside the insulating member 14, thereby housing the positive electrode layer 11 and the positive electrode side solid electrolyte layer 13a inside the insulating member 14. Next, the negative electrode piece was positioned with the negative electrode solid electrolyte layer 13b facing the positive electrode solid electrolyte layer 13a. At this time, in a plan view, the negative electrode active material layer 12c was positioned so that it was inside the outer surface of the frame-shaped insulating member 14. Subsequently, a uniaxial press was performed at a pressure of 120 MPa for one minute. Through the above process, 40 pole groups 1 were formed.

[0142] (Second process) In the second step, the AC resistance (ACR) was measured for each of the 40 pole groups 1 formed in the first step. The AC resistance was measured by measuring the current amplitude response under conditions of a frequency of 1 kHz and a voltage amplitude of 10 mV. Then, the standard deviation of the obtained AC resistance (ACR) measurement results was calculated, and the coefficient of variation of the AC resistance (ACR) of multiple pole groups 1 was calculated by dividing it by the mean value of the measurement results.

[0143] Next, from among multiple electrode groups 1, 40 set resistance electrode groups 1a were selected, in which the coefficient of variation of resistance value is 7% or less. Furthermore, in order to linearly approximate the relationship between the AC resistance value (ACR) of electrode group 1 used as the material for the electrode group laminate 10 and the set DC resistance (DCR) of the electrode group laminate 10 after chemical formation and discharge for 10 seconds to equation (1A) obtained in the above experimental example, 27 set resistance electrode groups 1a were selected from the 40 set resistance electrode groups 1a selected under the conditions shown below.

[0144] (conditions) The set DC resistance (DCR) "Y" in equation (1A) is 17 (Ωcm). 2 ) was determined. From among the multiple electrode groups 1 manufactured, those whose AC resistance value was within the range of 0.5Ω to 2.5Ω relative to the value of "X" calculated by formula (1A) were selected.

[0145] The 27 set resistor electrode group 1a selected in the second step have a coefficient of variation of the positive electrode active material layer weight of 0.8% or less. The coefficient of variation of the AC resistance (ACR) of the 27 set resistor electrode group 1a is 7.0% or less.

[0146] (Third step) In the third step, the 27 setting resistor electrode groups 1a selected in the second step were stacked. Next, the stacked setting resistor electrode groups 1a were connected in parallel to form a electrode group stack 10. Then, the positive electrode current collector tab 11b of the positive electrode layer 11 of the setting resistance electrode group 1a forming the electrode group laminate 10 was electrically connected, and the negative electrode current collector tab 12b of the negative electrode layer 12 was electrically connected.

[0147] Subsequently, the polar group laminate 10 was restrained using end plates, and a pressure of 3 MPa was applied in the stacking direction of the polar group laminate 10. Subsequently, the pole group laminate 10, which was restrained by the restraint jig, was housed in a case (not shown).

[0148] (Fourth step) In the fourth step, the polar group laminate 10 was formed by the method shown below. The polar group laminate 10 was formed under the conditions of a temperature of 60°C, a constraining load of 3 MPa, and an applied current of 0.1 C. By performing the above steps, a solid-state battery of Example 1 was obtained, in which 27 setting resistor electrode groups 1a were connected in parallel.

[0149] [Example 2] In the third step, a solid-state battery of Example 2 was obtained in the same manner as in Example 1, except that 12 setting resistor groups 1a were selected.

[0150] In the second step of Example 2, the selected group of 12 setting resistor electrodes 1a has a coefficient of variation of the positive electrode active material layer weight of 0.8% or less. The coefficient of variation of the AC resistance (ACR) of the group of 12 setting resistor electrodes 1a is 7.0% or less.

[0151] [Reference example 1] A single-cell solid-state battery of Reference Example 1 was obtained in the same manner as in Example 1, except that only one electrode group 1, manufactured in the same manner as in Example 1, was used.

[0152] Next, the specific capacity and resistance values ​​per positive electrode active material were measured for the solid batteries of Example 1, Example 2, and Reference Example 1 obtained in this manner, using the methods described below. The results are shown in Table 1.

[0153] [Method for measuring the specific capacity per positive electrode active material] The discharge capacity was measured in the voltage range of 2.65V-4.3V under conditions of a temperature of 60°C, a constrained load of 3MPa, and an applied current of 0.1C. The specific capacity was calculated by dividing the measured discharge capacity obtained in this way by the mass of the positive electrode active material used in the solid-state battery.

[0154] [Method for measuring resistance] At a temperature of 60°C, with a confinement load of 3MPa, a state of charge (SOC) of 50%, and a C rate ranging from 0.1C to 0.7C, current was applied for 10 seconds at each 0.1C increment, and the cell voltage was measured. For each C rate, the resistance value was calculated by dividing the absolute value of the decrease in cell voltage before and after current application by the current value, and the average resistance value for each C rate was used as the resistance value. The current value was calculated by multiplying the electrode group design capacity by the C rate. For example, if the electrode group design capacity is 150mAh, the current value at 0.1C is 15mA.

[0155] [Table 1]

[0156] As shown in Table 1, the solid-state battery of Example 1, in which 27 layers of setting resistance electrode groups 1a were stacked, and the solid-state battery of Example 2, in which 12 layers of setting resistance electrode groups 1a were stacked, had the same specific capacity and resistance value per positive electrode active material as the solid-state battery of Reference Example 1, which was a single cell. This confirmed that in Examples 1 and 2, the variation in resistance values ​​for each setting resistance electrode group 1a forming the electrode group stack 10 was suppressed. [Explanation of symbols]

[0157] 1... Electrode group, 1a... Setting resistance electrode group, 10... Electrode group laminate, 11... Positive electrode layer, 11a... Positive electrode current collector, 11b... Positive electrode current collector tab, 11c... Positive electrode active material layer, 12... Negative electrode layer, 12a... Negative electrode current collector, 12b... Negative electrode current collector tab, 12c... Negative electrode active material layer, 13... Solid electrolyte layer, 13a... Positive electrode side solid electrolyte layer, 13b... Negative electrode side solid electrolyte layer, 14... Insulating member.

Claims

1. A first step involves forming a group of electrodes including a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. A second step is to select multiple sets of set resistance electrodes from the plurality of electrode groups such that the coefficient of variation of the resistance values ​​of the plurality of electrode groups falls within a predetermined range. A third step involves stacking the aforementioned set resistor electrode groups to form an electrode group stack, A method for manufacturing a solid battery, comprising a fourth step of forming the aforementioned electrode group stack.

2. The method for manufacturing a solid battery according to claim 1, wherein the aforementioned resistance value is an AC resistance value.

3. A method for manufacturing a solid battery according to claim 1, wherein in the second step, multiple electrode groups are selected from the plurality of electrode groups such that the AC resistance value of the plurality of electrode groups falls within a predetermined range calculated in the fourth step based on the set DC resistance value of the electrode group stack after chemical formation and discharge for 10 seconds.

4. The method for manufacturing a solid battery according to claim 1, wherein in the second step, the electrode group stack is formed and multiple electrode groups are selected from the plurality of electrode groups such that the set DC resistance value when discharged for 10 seconds can be approximated as a function of the AC resistance value of the electrode group.

5. The method for manufacturing a solid battery according to claim 1, wherein in the second step, the electrode group stack is formed and multiple electrode groups are selected from the plurality of electrode groups such that the relationship between the set DC resistance value when discharged for 10 seconds and the AC resistance value of the electrode group can be linearly approximated.

6. The method for manufacturing a solid battery according to claim 1, wherein the resistance value is an AC resistance value and the coefficient of variation of the resistance value is 15% or less.

7. A method for manufacturing a solid battery according to claim 1, wherein the resistance value is an AC resistance value and the coefficient of variation of the resistance value is 10% or less.

8. The method for manufacturing a solid battery according to claim 1, wherein in the fourth step, the electrode group laminate is manufactured by chemically forming the electrode group laminate, thereby manufacturing an electrode group laminate in which the coefficient of variation of the DC resistance values ​​of the plurality of set resistance electrode groups forming the electrode group laminate is 10% or less.

9. In the fourth step, by forming the electrode group laminate, the DC resistance value at 60°C becomes 20 Ωcm. 2 A method for manufacturing a solid battery according to claim 1, comprising manufacturing the electrode group stack that is as follows:

10. The method for manufacturing a solid battery according to claim 1, wherein in the second step, multiple sets of set resistance electrodes are selected from the plurality of electrode groups such that the coefficient of variation of the capacity of the plurality of set resistance electrode groups is within a predetermined range.

11. A method for manufacturing a solid battery according to claim 10, wherein the coefficient of variation of the capacity is 5% or less.

12. The method for manufacturing a solid battery according to claim 10, wherein the coefficient of variation of the capacity is 3% or less.

13. The method for manufacturing a solid battery according to claim 1, wherein the negative electrode layer comprises lithium metal or a lithium alloy.

14. A solid battery manufactured by the manufacturing method described in claim 1.

15. It includes an electrode group laminate in which multiple electrode groups, each containing a positive electrode layer, a solid electrolyte layer, and a negative electrode layer, are stacked. The specific capacity per positive electrode active material of the aforementioned electrode group laminate is 150 mAh / g or more. The DC resistance of the aforementioned electrode stack at 60°C after 10 seconds of discharge is 18 Ω cm. 2 The following is a solid-state battery.

16. The specific capacity per positive electrode active material of the aforementioned electrode group laminate is 150 mAh / g or more. The DC resistance of the aforementioned polarity stacked material at 60°C after 10 seconds of discharge is 2 Ω cm. 2 The above is 17Ωcm 2 The solid battery according to claim 15, which is as follows:

Citation Information

Patent Citations

  • Battery Stack

    JP7622706B2

  • Solid-state battery and method for producing solid-state battery

    WO2019151376A1

  • Cell structure

    WO2019171905A1